Cleft Palate Repair with Orbicularis Oris Plus Buccal Mucosal Flap: A New Double Layered-Technique - Nihat Akbulut; Ahmet Altan; Esengul Sen (Shiraz University of Medical Sciences, 2023)
Recurrent oronasal fistula closure is a challenging phenomenon that has been managed with many surgical or flap techniques, such as local, regional, and distant flaps, with various modifications. Despite these options, the ideal method to repair this kind of chronic fistula has not yet been established. It is difficult to repair because recurrent surgical repairs or interventions cause this region to become more fibrotic with less vascular tissue, which considerably reduces the likelihood of closing this kind of fistula. For this reason, surgeons and researchers continue to work to overcome these obstacles by using more regional, vascular, and neighboring tissue. Classic cleft palate repair techniques use double-layered, nasal, and oral side closure and even a three-layered technique (e.g. plus levator veli palatini and tensor veli palatini muscular repair) in the soft palate region. Hence, we used partial orbicularis oris muscle with enough vascular supply to repair the nasal side and cheek mucosal flap to repair the oral side as a double-layered repair technique. Two years later, during routine patient follow-up, no complications were identified, and the patient's satisfaction with this treatment was acceptable.